What Leader should Do in Keeping Staff? Simplification of Human Resources Management Theory - Halimah Halimah; Ishak Bagea; Tri Indah Rusli; Nasir Nasir; Abubakar Abubakar; Muh. Takdir; Murniati Murniati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhhammadiyah kendari, 2022)
This study aims to develop a model of human resource retention to address the issue of workforce retention that has emerged as the most critical Human Resource Management challenge. It is based on a critical analysis of human resource trends which shows that a shortage of skilled employees will occur. Therefore, an appropriate strategy is needed to win the war or labor market competition. The researcher uses the Research & Development approach by adapting Kalk's spiral development model to the stages: definition, design, demonstration, development, and testing. Researchers involve human resource management experts and refer to previous concepts, theories and relevant previous studies for developing models. The Google Form Online Mailed Instrument was also used to see the responses of the respondents, totaling 128 people. The results of the study formulated the